Pengaruh Pengetahuan Investasi Terhadap Minat Mahasiswa Ekonomi Syariah UI BBC dalam Investasi Tabungan Emas Syariah - Abu Lubaba; Junemi; Ali Achmad Muhajir; Annisa Najwa Safira; Alfi Rahmah; Lintang Wijaya Kusuma (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
This study aims to examine the effect of investment knowledge on students' interest in choosing Islamic gold savings as an investment instrument. The discrepancy between the theoretical understanding of Islamic economics students and their low involvement in investment practices forms the basis for this study. Using a quantitative approach, 30 respondents were selected through purposive sampling. Data were obtained through a Likert scale questionnaire and analyzed using SPSS 27 through validity, reliability, normality, simple linear regression, and t-tests. The analysis results show that investment knowledge has a positive and significant effect on students' investment interest (calculated t 4.148 > table t 1.984; sig. < 0.001), with a contribution of 38.1% (R² = 0.381). This finding confirms that investment understanding is an important factor in shaping student interest, in line with the Theory of Planned Behavior framework.